Ultra-low dose abdominal MDCT: Using a knowledge-based Iterative Model Reconstruction technique for substantial dose reduction in a prospective clinical study. Issue 1 (January 2015) - Khawaja, Ranish Deedar Ali; Singh, Sarabjeet; Blake, Michael; Harisinghani, Mukesh; Choy, Garry; Karosmangulu, Ali; Padole, Atul; Do, Synho; Brown, Kevin; Thompson, Richard; Morton, Thomas; Raihani, Nilgoun; et al.
Highlights: Limited abdominal CT indications can be performed at a size specific dose estimate of (SSDE) 1.5 mGy (∼0.9 mSv) in smaller patients (BMI less than or equal to 25 kg/m 2 ) using a knowledge based Iterative Model Reconstruction (IMR) technique. Evaluation of liver tumors and pathologies is unacceptable at this reduced dose with IMR technique especially in patients with a BMI greater than 25 kg/m 2 . IMR body soft tissue and routine settings perform substantially better than IMR sharp plus setting in reduced dose CT images. At SSDE of 1.5 mGy, objective image noise in reduced dose IMR images is 8–56% less than compared to standard dose FBP images, with lowest image noise in IMR body-soft tissue images. Abstract: Purpose: To assess lesion detection and image quality parameters of a knowledge-based Iterative Model Reconstruction (IMR) in reduced dose (RD) abdominal CT examinations. Materials and methods: This IRB-approved prospective study included 82 abdominal CT examinations performed for 41 consecutive patients (mean age, 62 ± 12 years; F:M 28:13) who underwent a RD CT (SSDE, 1.5 mGy ± 0.4 [∼0.9 mSv] at 120 kV with 17–20 mAs/slice) immediately after their standard dose (SD) CT exam (10 mGy ± 3 [∼6 mSv] at 120 kV with automatic exposure control) on 256 MDCT (iCT, Philips Healthcare). SD data were reconstructed using filtered back projection (FBP). RD data were reconstructed with FBP and IMR. Four radiologists used a five-point scale (1 = image quality better than SD CT to 5 = image quality unacceptable) to assess both subjective image quality and artifacts. Lesions were first detected on RD FBP images. RD IMR and RD FBP images were then compared side-by-side to SD-FBP images in an independent, randomized and blinded fashion. Friedman's test and intraclass correlation coefficient were used for data analysis. Objective measurements included image noise and attenuation as well as noise spectral density (NSD) curves to assess the noise in frequency domain were obtained. In addition, a low-contrast phantom study was performed. Results: All true lesions (ranging from 32 to 55) on SD FBP images were detected on RD IMR images across all patients. RD FBP images were unacceptable for subjective image quality. Subjective ratings showed acceptable image quality for IMR for organ margins, soft-tissue structures, and retroperitoneal lymphadenopathy, compared to RD FBP in patients with a BMI ≤25 kg/m 2 (median-range, 2–3). Irrespective of patient BMI, subjective ratings for hepatic/renal cysts, stones and colonic diverticula were significantly better with RD IMR images ( P < 0.01). Objective image noise for RD FBP was 57–66% higher, and for RD IMR was 8–56% lower than that for SD-FBP ( P < 0.01). NSD showed significantly lower noise in the frequency domain with IMR in all patients compared to FBP. Conclusion: IMR considerably improved both objective and subjective image quality parameters of RD abdominal CT images compared to FBP in patients with BMI less than or equal to 25 kg/m 2 .